The use of Depletion Methods to assess Mediterranean cephalopod stocks under the current EU Data Collection Framework - KELLER, S.; ROBIN, J.-P.; VALLS, M.; GRAS, M.; CABANELLAS-REBOREDO, M.; QUETGLAS, A. (Mediterranean Marine Science, 2015)
Fuelled by the raising importance of cephalopod fisheries in Europe, there have been demands from scientists and stakeholders for their assessment and management. However, little has been done to improve the data collection in order to analyse cephalopod populations under the EU Data Collection Framework (DCF). While the DCF allows member states to design flexible national sampling programmes, it establishes the minimum data requirements (MDR) each state is obliged to fulfil. In this study, it was investigated whether such MDR currently set by the DCF allow the application of depletion models (DMs) to assess European cephalopod stocks. Squid and cuttlefish fisheries from the western Mediterranean were used as a case study. This exercise sheds doubt on the suitability of the MDR to properly assess and manage cephalopod stocks by means of DMs. Owing to the high plasticity of life-history traits in cephalopod populations, biological parameters should be estimated during the actual depletion period of the fished stocks, in contrast with the triennial sampling established by the DCF. In order to accurately track the depletion event, the rapid growth rates of cephalopods implies that their populations should be monitored at shorter time scales (ideally weekly or biweekly) instead of quarterly as required by the DCF. These measures would not demand additional resources of the ongoing DCF, but a redistribution of sampling efforts during the depletion period. Such changes in the sampling scheme could be designed and undertaken by the member states or directly integrated as requirements.